Charge Carrier Dynamics of SnO2 Electron‐Transporting Layers in Perovskite Solar Cells - Abraham Adenle; Selengesuren Suragtkhuu; Solongo Purevdorj; Yu Lin Zhong; Munkhbayar Batmunkh (Small Structures)
Perovskite solar cells (PSCs) have demonstrated remarkable increase in their photovoltaic efficiencies over the past several years. Charge carrier properties including charge selectivity, extraction, and transport play key roles in device performances. Therefore, a comprehensive insight into the charge carrier dynamics and mobility within the bulk materials and at the interface is of great importance for the future development of this cutting‐edge technology. This review discusses the recent advances that have been made in SnO2 electron‐transporting layers and their limitations, followed by outlining the key development of novel strategies in improving SnO2 films through surface defect engineering, interface modification, and doping approaches. In addition, the recent developments are highlighted for identifying the origin of defect and trap center, and promoting SnO2 electron extraction and transporting capacity in PSCs. Importantly, the novel approaches are also discussed for studying photogenerated charge carrier dynamics of the devices. In conclusion, the own prospectives and outlooks are presented for the development of SnO2‐based PSCs, with a particular focus on addressing current difficulties in SnO2 and providing in‐depth understanding on the relationships between materials and devices.